J. VAITKEVIČIUS ’ SCIENTIFIC ACTIVITIES AND METHODOLOGICAL ATTITUDES - Juodaitytė, Audronė (Acta Paedagogica Vilnensia, 2009)
Within this article J. Vaitkevičius’ scientific heritage is analysed and also his methodological-empirical attitudes and posittions are revealed as well. The critical analysis of his articles, monographs, study books is done and simultaneously some ideas of the development of reconstruction, existentialism, phenomenology, symbolic interaction are stressed along with the links to those philosophical streams’ fundamental researches. J.Vaitkevičius’ scientific contribution is evaluated while creating and forming new science branches in Lithuania: socio-cultural education, social pedagogy, comparing and historical pedagogy etc. J. Vaitkevičius concern for the science of education and the vision on Lithuanian education system future is discussed as well in this study. The article puts great emphasis on J.Vaitkevičius’contribution to the Lithuanian science of education with an encouragement to take an active part in the research of educational processes with the reference to J. Vaitkevičius scientific heritage.
Keywords: scientific activities; methodological approaches; education science branches